Dynamic relationships between psychological capital and adaptation in new military recruits: a longitudinal cross-lagged panel network analysis - Zhang, Qiao; Xu, Chen; Li, Min (Frontiers in Psychiatry, 2025)
New recruits face severe psychological problems due to military adaption. This study examined the dynamic interplay between psychological capital (PsyCap) and adaptation among recruits during their initial training period. A total of 988 male recruits were assessed at three time points over an 8-week period, with cross-lagged panel network (CLPN) analysis employed to model predictive pathways and identify key nodes. Optimism had the strongest impact on the early adaptation (T1→T2), acting as a central linking bridge between PsyCap and the adaptation dimensions. Later in the T2→T3 stage, hope emerged as the strongest predictor, especially in relation to the reduction of the physical and psychological symptoms and an improvement in the role cognition. Resilience was a robust predictor of symptom improvement. The results reveal evolving roles of PsyCap components during adaptation, highlighting the importance of targeted interventions for enhancing adaptation among new recruits.